Pengaruh Design, Kualitas Layanan, Motivasi Terhadap Keputusan Pembelian Sepeda Motor Honda Scoopy (Studi Kasus Konsumen Honda Surya Gemilang Motor Lamongan) - Bahtiar, Dimas Vigo; Asiyah, Siti; Primanto, Alfian Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to analyze the influence of brand image, online customer reviews, and celebrity endorsements on the purchasing decisions of the Facial Wash Kahf product among students of the Faculty of Economics and Business (FEB) at the Islamic University of Malang. The research uses a quantitative approach with an explanatory research method. The population of this study comprises FEB students who use Facial Wash Kahf, with a sample of 100 respondents obtained using purposive sampling based on the Malhotra formula. Data were collected through questionnaires and analyzed using the coefficient of determination test. The results show that brand image, online customer reviews, and celebrity endorsements simultaneously have a significant impact on purchasing decisions. Partially, online customer reviews and celebrity endorsements significantly influence purchasing decisions, while brand image does not. The Adjusted R Square of 68.8% indicates that the dependent variable, namely purchasing decisions, can be explained by brand image, online customer reviews, and celebrity endorsements, while 31.2% is explained by other variables outside the research model. The conclusion of this study is that brand image, online customer reviews, and celebrity endorsements significantly influence the purchasing decisions of the Facial Wash Kahf product, with online customer reviews and celebrity endorsements having a stronger partial influence. Keywords: Brand Image, Online Customer Reviews, Celebrity Endorsements, Purchasing Decisions, Facial Wash Kahf.